IDENTIFIKASI DERAJAT KOMPETISI FISKAL KABUPATEN/KOTA DI JAWA TIMUR - Bintang Dwitya Cahyono (Jurnal Ekonomi dan Pembangunan, 2025)
Fiscal decentralization has been implemented by Indonesian’s government since 2001. Decentralized system encourage local governments/ municipality to be more independent and creative in managing fiscal policy in their regions. The interaction of fiscal policy strategy in the region caused fiscal competition between regions. The purpose of this study is to measure the degree of fiscal competition amongs local governments in East Java divided into five economic corridors: (1) Eastern Corridor, (2) Central Corridor, (3) Southwest Corridor, (4) West Corridor; and (5) Corridor Islands. By using the Fuzzy Logic approach, the study found that the Central Corridor has the highest degree of fiscal competition in East Java.